2008
DOI: 10.1158/1535-7163.mct-08-0420
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin SK modulates polyploidy and cell death in colon carcinoma cells

Abstract: During a normal cell cycle, polyploidy and aneuploidy can be prevented by several checkpoints, which are mainly p53 dependent. Here, we show that treatment of HCT-116 (p53 +/+ ) colon carcinoma cells with the novel antitumor antibiotic mithramycin SK (MSK) results in polyploidization and mitotic catastrophe, which occurs after a transient halt in G 1 phase followed by the overtaking of the G 2 -M checkpoint when treated cells are incubated in a fresh drug-free medium. Cells reentering aberrant mitosis mainly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…4) and low dose of rapamycin (1 nmol/L) potentiated mithramycin sensitivity (1.5-fold in G 2 -M population and 2-fold in G 2 -M period time, 2xGI 50 , 48 hours). It was reported that p53 status played an important role in modulation of mithramycin-induced cell polyploidy and cell death in colon carcinoma cells (25). Mithramycin SK, a novel analog of mithramycin, results in polyploidization and mitotic catastrophe in HCT116 cells with wt p53 and most cell populations died by necrosis, whereas HCT-116 (p53 À/À ) cells died mainly from G 2 -M block through early p53-independent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…4) and low dose of rapamycin (1 nmol/L) potentiated mithramycin sensitivity (1.5-fold in G 2 -M population and 2-fold in G 2 -M period time, 2xGI 50 , 48 hours). It was reported that p53 status played an important role in modulation of mithramycin-induced cell polyploidy and cell death in colon carcinoma cells (25). Mithramycin SK, a novel analog of mithramycin, results in polyploidization and mitotic catastrophe in HCT116 cells with wt p53 and most cell populations died by necrosis, whereas HCT-116 (p53 À/À ) cells died mainly from G 2 -M block through early p53-independent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Protein was extracted from doxorubicin-treated and control cells as described elsewhere [21]. A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 6 The final fate of doxorubicin-treated HCT116 (p53 +/+ ) cells was analyzed at different times by using a clonogenic assay, according to a protocol described elsewhere [37], with minor modifications that included using 5% Giemsa (Sigma) for cell staining.…”
Section: Western Analysis Of Protein Levelsmentioning
confidence: 99%
“…Several DNA-binding drugs have been reported to produce mitotic catastrophe in both cells containing wild-type p53 and those bearing mutated or deleted p53 genes [13][14][15][16][17]. Mitotic catastrophe occurs in tumor cells treated with various antitumour drugs or radiation [7,13,14,[16][17][18][19][20][21]. These antitumour agents can also limit tumor growth through accelerated senescence arrest [10,12,13,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because tumor cells are frequently deficient in factors controlling the cell-cycle checkpoints, particularly functional p53, they may be predisposed to mitotic catastrophe after chemotherapy [1,5,6]. DNA damage combined with G2/M checkpoint deficiency leads cells to multinucleation, which may be followed by cell death [1,3,7]. Apoptosis and necrosis have been observed following multinucleation [8][9][10][11], and it has been proposed that mitotic catastrophe might not constitute a "genuine" cell death mechanism, but an oncosuppressive pathway that can precede cell death [12,13].…”
Section: Introductionmentioning
confidence: 99%